Collaborative Visualization Framework for Cross-field Working Group: A Qualitative Focus Group Study - Hasni, D.I.M. (Institute of Electrical and Electronics Engineers Inc., 2020)
This study is conducted to develop a collaborative visualization framework in the cross-field working group. The ultimate goal of this project is to provide a proper framework that can be used to develop a platform to allow collaborative visualization to be implemented inter-disciplinary groups, in two different settings; university students and research groups in research and development companies and institutions. The study begins with preliminary works to define the collaborative visualization based on previous researches. This study will also focus on the factors to develop an effective collaborative working environment thru visualization and shared understanding among the staffs/users from inter-disciplinary backgrounds. In addition, this study will also investigate the interaction between human cognition and ICT attributes of visualization in developing an efficient working group to achieve a common goals and objectives. Towards the end of the study, the framework will be tested to validate its possible contributions to the targeted collaborative working groups. Â© 2020 IEEE.